9.8k views
6 votes
What is the solution to the equation 6x + 2(x − 3) = 4x + x − 18? (1 point) 4 2 −2 −4​

User Paisal
by
5.2k points

2 Answers

1 vote

Answer:

x = -4

If that's not what you are looking for, please tell me :)

Explanation:

Distribute

2(x-3)

Combine Like Terms

6x+2x

Combine like terms

(4x + x)

User Gregw
by
5.0k points
6 votes

Answer:

see below for explanation:-�

Explanation:


: \implies 6x + 2(x - 3) = 4x + x - 18


: \implies{6x + 2x - 6 = 4x + x - 18}


: \implies{8x - 6 = 5x - 18}

  • Add 6 to the both sides:-


: \implies{8x - 6 + 6 = 5x - 18 + 6}


: \implies{8x = 5x - 12}

  • Subtract 5x from both sides:-


: \implies{8x - 5x = 5x - 12 - 5x}


: \implies{8x - 5x = 5x - 5x - 12}


: \implies{3x = 0 - 12}


: \implies{3x = - 12}

  • Divide both sides by 3:-


: \implies{ \displaystyle{ (3x)/(3) = ( - 12)/(3) }}


: \implies{x = - 4}

User Ken Richards
by
5.4k points